A para-nitrophenol phosphonate probe labels distinct serine hydrolases of Arabidopsis. - Nickel, S; Kaschani, F; Colby, T; van der Hoorn, R; Kaiser, M (2012)
Activity-based protein profiling represents a powerful methodology to probe the activity state of enzymes under various physiological conditions. Here we present the development of a para-nitrophenol phosphonate activity-based probe with structural similarities to the potent agrochemical paraoxon. We demonstrate that this probes labels distinct serine hydrolases with the carboxylesterase CXE12 as the predominant target in Arabidopsis thaliana. The designed probe features a distinct labeling pattern and therefore represents a promising chemical tool to investigate physiological roles of selected serine hydrolases such as CXE12 in plant biology.